Process optimization and kinetics for leaching of rare earth metals from the spent Ni-metal hydride batteries - Meshram P.; Pandey B.D.; Mankhand T.R. (My University, 2025)
Nickel-metal hydride batteries (Ni-MH) contain not only the base metals, but valuable rare earth metals (REMs) viz. La, Sm, Nd, Pr and Ce as well. In view of the importance of resource recycling and assured supply of the contained metals in such wastes, the present study has focussed on the leaching of the rare earth metals from the spent Ni-MH batteries. The conditions for the leaching of REMs from the spent batteries were optimized as: 2 M H2SO4, 348 K temperature and 120 min of time at a pulp density (PD) of 100 g/L. Under this condition, the leaching of 98.1% Nd, 98.4% Sm, 95.5% Pr and 89.4% Ce was achieved. Besides the rare earth metals, more than 90% of base metals (Ni, Co, Mn and Zn) were also leached out in this condition. Kinetic data for the dissolution of all the rare earth metals showed the best fit to the chemical control shrinking core model. The leaching of metals followed the mechanism involving the chemical reaction proceeding on the surface of particles by the lixiviant, which was corroborated by the XRD phase analysis and SEM-EDS studies. The activation energy of 7.6, 6.3, 11.3 and 13.5 kJ/mol was acquired for the leaching of neodymium, samarium, praseodymium and cerium, respectively in the temperature range 305-348 K. From the leach liquor, the mixed rare earth metals were precipitated at pH ~ 1.8 and the precipitated REMs was analyzed by XRD and SEM studies to determine the phases and the morphological features. © 2015.